ANALISIS KEMAMPUAN KOGNITIF SISWA KELAS X SMA NEGERI 3 RAMBAH HILIR KABUPATEN ROKAN HULU PADA MATA PELAJARAN FISIKA SETELAH PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER BERBASIS MIND MAP - AFYUNI, CICI; HATIKA, RINDI GENESA; RITA, SILVIA (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
This study aims to determine the ability and cognitive criteria for students in physics learning using model Advance Organizer base on Mind Map. This research method is a quasi-experimental research conducted at SMA Negeri 3 Rambah hilir class X MIA . The sampling technique that is done is saturated sampling. After learning model Advance base on Organizer Mind Map is applied, the cognitive abilities of students has increased. It is shown from the results of student learning is the lowest gain value is 0.667 (medium criterion) and the highest gain value of 0.8 (high criteria) . While the criteria of students cognitive abilities of the average value in the classical style in the entire series is 0.712 (high criteria)